Combined pathogenetic therapy of erectile dysfunction - S. S. Krasnyak; E. A. Efremov (Вестник урологии)
Introduction. Erectile dysfunction (ED) is a common condition that reduces the quality of life of numerous men. Therefore, optimising treatment protocols is always a challenge.Objective. To evaluate the efficacy of "Edelim®" for pathogenetic therapy for erectile dysfunction.Materials and methods. The study included 67 men (40 – 65 years old) with ED. The patients were divided into two treatment groups: the main group received tadalafil 5 mg PO o.d. + “Edelim®”, the control group received tadalafil 5 mg PO o.d. only. As effectiveness criteria anthropometric studies were used, IIEF-5 scale, metabolic profile blood tests, and systemic endothelial function was assessed.Results. Over 12 months of therapy, the IIEF-5 score increased by 28.2% in the main group and by 10.3% in the control group. After 12 months in the main group total cholesterol, LDL, triglycerides decreased by 14.8%, 10.7% and 13.9% respectively. The reactive hyperaemia index after 3, 6 and 12 months increased by 6.6%, 10.9% and 22.0%, respectively. In the control group these indices did not change significantly. The main group showed a stable decrease in body mass and waist circumference by an average of 2.6% and 3.8% respectively after 12 months. In the control group, body mass did not change significantly.Conclusion. Some patients require combination therapy to address metabolic risk factors and disorders, despite the high efficacy of PDE-5 inhibitors in improving erection quality. “Edelim®” is the first product created specifically for long-term combined pathogenetic therapy of ED with metabolic disorders.